Pengaruh Peranan Audit Internal dan Pengendalian Internal terhadap Pencegahan Fraud - Saipul Hajat; Eka Rima Prasetya (Universitas Pamulang, 2020)
The purpose of this study was to determine the effect of the role of internal audit and internal control on the prevention of fraud cases at PT. Tunas Toyota branch operating in Ciputat This type of research uses quantitative methods. This study uses a saturated sample technique in determining the number of samples. The study used primary data with survey techniques, namely by giving questionnaires to employees who work at PT. Tunas Toyota branch operating in Ciputat. The population in this study are all employees who work at the Ciputat branch office. The data analysis technique used multiple regression analysis. The results of the study prove that the role of internal audit and internal control simultaneously has an effect on fraud prevention. Partially, the role of internal audit has an effect on fraud prevention. Internal audits carried out by companies play an important role in preventing fraud. While internal control has an effect on fraud prevention, this proves that internal control within the company is a very important part of preventing fraud. Keywords: Role of Internal Audit, Internal Control, Fraud Prevention